Dynamic processes in road designs highways - A. V. Smirnov; E. V. Andreyev; V. F. Ignatov (Вестник СибАДИ)
The models loading layers of the multilayer road construction under the influence of the moving vertical load was reviewed, as well as forms of forced and natural vibrations. By numerical analysis are set to dynamic deflection, the speed and acceleration of vibration, dynamic compressive stress - strain, which is a measure of strength, also a benchmark for testing road construction materials on endurance